Landing of India-Asia-Xpress (IAX) undersea cable system in Maldives - Reliance Industries Limited (2022)
Jio, working with the Government of Maldives, lands the next generation multi-terabit India-Asia-Xpress (IAX) undersea cable system in Hulhumalé, Maldives, which will connect the Maldives directly with the world's major internet hubs in India and Singapore.